Effect of extruded wheat flour and pre-gelatinized cassava starch on process and quality parameters of French-type bread elaborated from frozen dough - Ortolan, Fernanda; et al. (2015)
This study aimed to verify the potential of extruded wheat flour (EWF) or pre-gelatinized cassava starch (PGS) to improve the process and the quality of French bread elaborated from frozen dough. Three formulations were prepared: 100% control wheat flour (CWF) and the other two formulations with 5% substitution of wheat flour by EWF or PGS. Frozen doughs were frozen stored for seven days and after this period they were thawed, fermented, baked and evaluated for physical, chemical and technological characteristics. Available glucose levels found for EWF (12 g/100 g), and PGS (11.7 g/100 g) in relation to CWF (7.1 g/100 g) showed higher sugar availability for yeasts at the initial stage of proofing, and may also have had a cryoprotective effect when freezing bread doughs. The frozen doughs with EWF or PGS, when thawed and fermented, presented higher volume increase, but after baking, they presented lower volume when compared to the control bread. The results of this study are promising for the use of extruded wheat flour or pre-gelatinized cassava starch as sugar providers for doughs' post-freezing proofing process, improving frozen dough process of French-type bread. © 2015 Elsevier Ltd. All rights reserved.